Business analytics for Sales and Marketing Managers : How to Compete in the Information Age - Laursen, Gert H. N. (Hoboken, New York : John Wiley & Sons, 2011)
'Expert guidance on information management for optimum customer intelligence processes Providing essential guidance for information management, this book helps you understand the basics of information management, how to design and launch customer intelligence campaigns, and optimize existing customer intelligence processes. How to align information management with company strategy Examines how to get, grow, and retain valuable customers Discusses how to optimize existing customer intelligence processes Showing you how to make extensive use of data, statistical, and quantitative analysis, explanatory and predictive modeling, and fact-based management to drive decision making, Business Analytics for Customer Intelligence provides you with the tools your business needs to optimize you data driven processes'--
Includes bibliographical references and index.
Keywords: Consumers' preferences -- Research; Consumers -- Research